Zwierzęta pozaludzkie jako podmioty polityki. Koncepcja zoopolis i jej krytyka - Gzyra, Dariusz (Zoophilologica. Polish Journal of Animal Studies, 2016)
The interests of nonhuman animals within political philosophy have been and are still overlooked and underestimated. Recognition by modern science, and – increasingly – ethics, of the subjectivity and vulnerability of many animals does not extend to recognizing them as anything more than a secondary object of politics. In recent years, however, new concepts have emerged emphasizing the subjectivity and political agency of nonhuman animals. One of them is the concept of zoopolis by Sue Donaldson and Will Kymlicka. It postulates the use of political and legal categories that previously defined only men: citizenship, denizenship and sovereignty. Through citing earlier attempts at politicization of the animal detriment issue, the article presents the major hypothesis of the zoopolis concept and discusses some examples of its previous criticism.